Dynamic First Tarsometatarsal Instability During Gait Evaluated by Pedobarographic Examination in Patients with Hallux Valgus - Byung Jo Min; Seungbum Koo PhD; Won-keun Park; Ki-bum Kwon; Kyoung Min Lee MD, PhD (Foot & Ankle Orthopaedics, 2019)
Category: Midfoot/Forefoot Introduction/Purpose: This study aimed to investigate the pedobarographic characteristics of tarsometatarsal instability and to identify factors associated with pedobarographic first tarsometatarsal instability in patients with hallux valgus deformity. Methods: Fifty-seven patients (mean age, 59.7 years; standard deviation, 11.4 years; 6 men and 51 women) with a hallux valgus angle (HVA) greater than 15° were included. All patients underwent a pedobarographic examination along with weight-bearing anteroposterior (AP) and lateral foot radiography. Radiographic measurements were compared between the two groups with and without pedobarographic first tarsometatarsal instability. The association between the radiographic and pedobarographic parameters of the first tarsometatarsal instability was analyzed using the chi-square test. Binary logistic regression analysis was performed to identify significant factors affecting pedobarographic first tarsometatarsal instability. Results: HVA (p<0.001), the intermetatarsal angle (p=0.001), and AP talo-first metatarsal angle were significantly different between the pedobarographically stable and unstable tarsometatarsal groups. There was no significant association between radiographic and pedobarographic instabilities of the first tarsometatarsal joint (p=0.924). HVA was found to be the only significant factor affecting pedobarographic tarsometatarsal joint instability (p=0.001). Conclusion: The pedobarographic examination has possible clinical utility in evaluating first tarsometatarsal joint instability in patients with hallux valgus deformity. Patients with greater HVA need to be carefully monitored for the presence of first tarsometatarsal instability, and the necessity of the Lapidus procedure should be considered.